A randomised crossover trial of facemask efficacy. Issue 1 (7th January 2004) - Hayden, J T; Smith, N; Woolf, D A; Barry, P W; O'Callaghan, C
Abstract : The efficacy of different facemasks that can be used in the delivery of aerosol medication to children with recurrent wheeze or asthma was investigated. The results showed a statistically significant difference between some of the masks used, which has important implications for current clinical practice